G2P1A0 Hamil 39 Minggu Inpartu Kala I Fase Aktif Memanjang JTH Preskep: Sebuah Laporan Kasus - Reva Dwi Yanty; fahmi ikhtiar; Nurul Islamy (Medula, 2022)
Maternal mortality rate (MMR) is one of several parameters that can describe the welfare of society in a country, especially developing countries such as Indonesia. One of the causes of maternal death is caused by prolonged delivery. Long labor is the 5th leading cause of maternal death both in Indonesia and in the world. The factors for the occurrence of prolonged labor are divided into two factors, namely causative and risk factors, causative factors: his, mal presentation and mal position, large fetus, narrow pelvis, cervical and vaginal abnormalities, fetovelvic disproportion, and premature rupture of membranes, and risk factors: excessive analgesia and analgesia, parity, age, dependent woman, stress response, restriction of mobility, and strict fasting. Mrs. NS was pregnant at term, 26 years old with complaints of heartburn since 18 hours before being admitted to the hospital. Initially, the heartburn was felt at 04.00 WIB and until 22.00 WIB there was still an 8 cm opening. On obstetric examination, external examination revealed that the height of the uterine fundus was 32 cm, the upper part of the fetus was palpable buttocks, the left side of the mother was palpated for the back, the lower part of the head was palpated into the pelvic inlet (PAP) or the fifth was 2/5. Fetal Heart Rate 136 x/minute and Estimated Fetal Weight 3100 grams. On internal examination, it was found that 90% flattened, 9 cm dilatation, hodge III, station 0. The management of this patient was vaginal termination of pregnancy.